Exploring The Role of The U.S. In The UN Securlty Council - Dib Fatima Zahra; Khamida Hania (University of El-Oued جامعة الوادي, 2025)
تحقق هذه الدراسة في دور الولايات المتحدة في مجلس الأمن التابع للأمم المتحدة. من خلال تحليل استخدامها الاستراتيجي لحق النقض (الفيتو)، وتدخلاتها العسكرية الأحادية، ونُظُم العقوبات في تشكيل حوكمة الأمن العالمي من الحرب الباردة إلى العصر متعدد الأقطاب الحالي. و من خلال منهج وصفيٍّ تحليليٍّ وعبرَ تقصٍّ نوعيٍّ، تحلل الدراسة بشكل منهجي سلوك الولايات المتحدة اتجاه قراراتِ مجلس الأمن. يتضمن هذا المنهج استقراء البياناتِ الأولية كالوثائق الرسمية للأمم المتحدة لتقديم نظرة عامة شاملة لتأثير الولايات المتحدة وقوتها المؤسسية بشؤون الأمن العالمي. إذ تتمتع الولايات المتحدة بدور فريد ومهيمن في مجلس الأمن التابع للأمم المتحدة نظرا لكونها شريكا مؤسسا، وعضوا دائما يتمتع بحق النقض (الفيتو) وقوة مالية لوجستية هائلة داعمة للأمم المتحدة. الكلمات المفتاحية:  تحقق هذه الدراسة في دور الولايات المتحدة في مجلس الأمن التابع للأمم المتحدة. من خلال تحليل استخدامها الاستراتيجي لحق النقض (الفيتو)، وتدخلاتها العسكرية الأحادية، ونُظُم العقوبات في تشكيل حوكمة الأمن العالمي من الحرب الباردة إلى العصر متعدد الأقطاب الحالي. و من خلال منهج وصفيٍّ تحليليٍّ وعبرَ تقصٍّ نوعيٍّ، تحلل الدراسة بشكل منهجي سلوك الولايات المتحدة اتجاه قراراتِ مجلس الأمن. يتضمن هذا المنهج استقراء البياناتِ الأولية كالوثائق الرسمية للأمم المتحدة لتقديم نظرة عامة شاملة لتأثير الولايات المتحدة وقوتها المؤسسية بشؤون الأمن العالمي. إذ تتمتع الولايات المتحدة بدور فريد ومهيمن في مجلس الأمن التابع للأمم المتحدة نظرا لكونها شريكا مؤسسا، وعضوا دائما يتمتع بحق النقض (الفيتو) وقوة مالية لوجستية هائلة داعمة للأمم المتحدة. Abstract This study examines the role of the U.S. in the UNSC, analyzing how its strategic use of veto power, unilateral military interventions, and sanctions regimes has shaped global security governance from the Cold War to today’s multipolar era. Through a qualitative methodology and a descriptive-analytical approach, the study systematically analyzes of UNSC resolutions, and the U.S. decisions towards UNSC. This approach involves an examination of primary data such as official UN documents to provide a comprehensive overview of the U.S. impact on international security governance. The results confirm a more nuanced picture of U.S. hegemony and institutional power concerning security in the world. The U.S. has a unique and predominant role in the UN Security Council due to being a founding partner, a permanent veto-wielding member, and a financial and logistical powerhouse for the UN. Abstract This study examines the role of the U.S. in the UNSC, analyzing how its strategic use of veto power, unilateral military interventions, and sanctions regimes has shaped global security governance from the Cold War to today’s multipolar era. Through a qualitative methodology and a descriptive-analytical approach, the study systematically analyzes of UNSC resolutions, and the U.S. decisions towards UNSC. This approach involves an examination of primary data such as official UN documents to provide a comprehensive overview of the U.S. impact on international security governance. The results confirm a more nuanced picture of U.S. hegemony and institutional power concerning security in the world. The U.S. has a unique and predominant role in the UN Security Council due to being a founding partner, a permanent veto-wielding member, and a financial and logistical powerhouse for the UN.
Keywords: الولايات المتحدة، ، مجلس الأمن التابع للأمم المتحدة ، حق الفيتو عقوبات; U.S.; hegemony; UNSC; veto power. Sanctions